2008
DOI: 10.1158/0008-5472.can-08-0287
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy Targeting the High Molecular Weight Melanoma-Associated Antigen Protein Results in a Broad Antitumor Response and Reduction of Pericytes in the Tumor Vasculature

Abstract: The high molecular weight melanoma-associated antigen (HMW-MAA), also known as melanoma chondroitin sulfate proteoglycan, has been used as a target for the immunotherapy of melanoma. This antigen is expressed on the cell surface and has a restricted distribution in normal tissues. Besides its expression in a broad range of transformed cells, this antigen is also found in pericytes, which are important for tumor angiogenesis. We generated a recombinant Listeria monocytogenes (Lm-LLO-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 49 publications
0
72
0
Order By: Relevance
“…This Listeria-LLO-HMW-MAA vaccine was able to slow the growth of a number of transplanted subcutaneous tumor cells, reduce the appearance of micrometastases in a lung seeding model and slow the appearance of breast tumors in a transgenic mouse model for breast cancer. 69 In addition, the vaccine induced a significant reduction in tumor volume, MVD and pericyte coverage, which correlated with an increase in CD8 T-cell infiltration into the tumor microenvironment. However targeting HMW-MAA did not appear to influence the ability of mice to lay down normal tissue vasculature during pregnancy or wound healing 69 indicating that it had few adverse effects.…”
Section: Ros-mediated Tumor Cell Kill By Listeriamentioning
confidence: 90%
See 1 more Smart Citation
“…This Listeria-LLO-HMW-MAA vaccine was able to slow the growth of a number of transplanted subcutaneous tumor cells, reduce the appearance of micrometastases in a lung seeding model and slow the appearance of breast tumors in a transgenic mouse model for breast cancer. 69 In addition, the vaccine induced a significant reduction in tumor volume, MVD and pericyte coverage, which correlated with an increase in CD8 T-cell infiltration into the tumor microenvironment. However targeting HMW-MAA did not appear to influence the ability of mice to lay down normal tissue vasculature during pregnancy or wound healing 69 indicating that it had few adverse effects.…”
Section: Ros-mediated Tumor Cell Kill By Listeriamentioning
confidence: 90%
“…69 In addition, the vaccine induced a significant reduction in tumor volume, MVD and pericyte coverage, which correlated with an increase in CD8 T-cell infiltration into the tumor microenvironment. However targeting HMW-MAA did not appear to influence the ability of mice to lay down normal tissue vasculature during pregnancy or wound healing 69 indicating that it had few adverse effects. Taken together these studies suggest that Listeria can break tolerance to ubiquitous self-molecules and destroy tumor vasculature with little consequence to normal vasculature indicating that this may be a promising approach for tumor immunotherapy.…”
Section: Ros-mediated Tumor Cell Kill By Listeriamentioning
confidence: 90%
“…Recently, Maciag et al reported that targeting the pericytes in tumor vasculature can inhibit the growth of tumors (including renal carcinoma) in animal models. 61 In fact, combined therapy targeting both endothelial cells and pericytes has been proposed for clinical trials.…”
Section: Future Targets For Antiangiogenic Therapymentioning
confidence: 99%
“…The reason why Rerum ® could be considered the new Coley's vaccine lays in the consideration that Coley's vaccine was a rudimentary, albeit tremendously efficient, combination of immunotherapy and direct anti-cancer effects that is replicated, in a more controlled and safe manner, by Rerum ® . Thus, each one of the molecules constituting Rerum ® is endowed both with immunomodulating and anti-cancer properties that, in many cases have been known for centuries as it was described for oleic acid, jokingly dubbed "... anti-oncogenes nutraceuticals since the 17th Century" (Maciag et al, 2008). Although the immunomodulating and anti-cancer properties of chondroitin sulfate, vitamin D 3 and oleic acid have been known for, at least, decades, Rerum ® adds a novel feature that is due to the assembly of the three molecules in one single tridimensional supramolecular structure.…”
Section: The Development Of a Novel Approach To Glycosaminoglycan-basmentioning
confidence: 99%